Pengembangan Perangkat Pembelajaran Strategi IDEAL Problem Solving Berbantuan Puzzquare Materi Luas Daerah Segiempat Kelas VII (Kreano, Jurnal Matematika Kreatif-Inovatif, 2011)
This research is classified as the developmental research. It develops learning materials using IDEAL problem solving strategy supported by Puzzquare for quadrilateral area for grade VII. The goals of this research are the development of learning materials using IDEAL problem solving strategy supported by Puzzquare is valid and learning process using that materials is effective. The development of learning materials on this research used 4-D model (Thiagarajan, Semmel and Semmel): (1) Define, (2) Design, (3) Develop, and (4) Disseminate. The developed learning-materials are (1) syllabus (2) lesson plan, (3) handbook, (4) student activity sheet, and (5) problem solving ability test. Keyword: The Development of Learning Material, IDEAL Problem Solving, Puzzquare